Pembentukan Bank Sampah dan Pengelolaan Tong Sampah Gotong Royong (Banktopgoyong ) Sebagai Solusi Pengurangan Sampah dan Peningkatan Ekonomi Masyarakat Desa Godog, Kabupaten Sukoharjo - Hartanto, Rima Vien Permata; Carista, Firnindita Nandya; Nugrahaning, Warda Saniyya; Krisdiyanto, Esananda; Istiqomah, Mifthah; Fikriyah, Febriana Wati (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Banktopgoyong is a community-based waste management initiative in Godog Village, Sukoharjo, which integrates the concept of waste banks and gotong royong waste bins. The selection of this topic is based on the importance of sustainable waste management to reduce environmental pollution, improve the community's economy, and build village independence. The service method includes socialization, waste management training, regular waste collection, and community empowerment to sort and exchange waste into money. The results of the activity show that there is an increase in public awareness of waste management, a reduction in the volume of waste at the Final Disposal Site (TPA), and an increase in residents' income through waste economy activities. The conclusion shows that community-based waste management such as Banktopgoyong is effective in improving the welfare and sustainability of the village environment, so it is important to develop and expand to other villages as an independent and sustainable waste management solution.